2021
DOI: 10.1371/journal.pone.0246055
|View full text |Cite
|
Sign up to set email alerts
|

Identifying bedrest using waist-worn triaxial accelerometers in preschool children

Abstract: Purpose To adapt and validate a previously developed decision tree for youth to identify bedrest for use in preschool children. Methods Parents of healthy preschool (3-6-year-old) children (n = 610; 294 males) were asked to help them to wear an accelerometer for 7 to 10 days and 24 hours/day on their waist. Children with ≥3 nights of valid recordings were randomly allocated to the development (n = 200) and validation (n = 200) groups. Wear periods from accelerometer recordings were identified minute-by-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Actigraph and Actical accelerometers have most frequently been validated and worn using a hip placement [ 56 , 57 , 58 ]; however, both hip and wrist placements have shown potential to classify intensity of movement in pre-school children [ 47 ]. The findings of the present study showed variation in terms of preference between wrist and hip; with wrist being said to be feasible if the device can be worn like a watch, and the hip placement if the device is under the clothes then children are more likely to forget about it.…”
Section: Discussionmentioning
confidence: 99%
“…Actigraph and Actical accelerometers have most frequently been validated and worn using a hip placement [ 56 , 57 , 58 ]; however, both hip and wrist placements have shown potential to classify intensity of movement in pre-school children [ 47 ]. The findings of the present study showed variation in terms of preference between wrist and hip; with wrist being said to be feasible if the device can be worn like a watch, and the hip placement if the device is under the clothes then children are more likely to forget about it.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with at least 500 min of wear per day and 3 wear-days will be included for analysis. A sleep period, defined based on mother-reported sleep onset (bedtime) and sleep offset (waking time), will be identified based on a sleep algorithm developed by Tracy et al [ 52 ]. The wear time log sheet will also be used to cross-check non-wear and sleep periods.…”
Section: Methodsmentioning
confidence: 99%
“…One study assessing criterion validity was quality assessed as inadequate (50) due to the type of analysis conducted. The majority of studies assessing the convergent validity of the tools were quality assessed as high risk of bias; eight inadequate (34,35,37,(51)(52)(53)(54)56) and four doubtful (36,57,59,60), with the exception of one study quality assessed as very good (61). Main reasons for poor methodological quality of the studies was due to unknown measurement properties of the comparator tools.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…One study examined the ability of the Actigraph GT3X+ accelerometer to determine bedrest and wake time, using a newly developed decision tree algorithm specific to pre-school aged children (57). The developed algorithm was able to detect bedrest and wake time similarly to visual identification of the data and was better at identifying bedrest than algorithms developed in other age groups that are often applied to young children (63,64).…”
Section: Convergent Validity Accelerometersmentioning
confidence: 99%
See 1 more Smart Citation